Optimasi Sistem Usahatani Campuran pada Anggota Kelompok Tani Catur Amerta Sari di Desa Sebudi, Kecamatan Selat, Kabupaten Karangasem - I GEDE JANUARTHA; I WAYAN BUDIASA; M. TH. HANDAYANI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2012)
ABSTRACT Optimalization of Farming System on Members of Catur Amerta Farmer Group in Sebudi Village, Selat District, Karangasem Regency The development of agriculture in this time strived to realize agriculture vision 2025 which aims to sustainable agriculture and can guarantee food resilience and also prosperity of farmer. One of the way to reached the vision is by optimization the integrated farming system that conducted by all farmer, including in Bali, especially in Karangasem Regency. Accordingly, a research is needed on farmer group member of Catur Amerta Sari in Sebudi Village, Selat District, Karangasem Regency. This research aims to know the actual earnings, the optimal model, and maximum earnings of integrated farming system which obtained with analysis of optimization toward 28 farmer group member of Catur Amerta Sari. Integrated farming system that conducted by responder is chili, tomato, gumitir flower, cabbage, and cattle rearing. Data type that used is data qualitative and quantitative, while data collected used field study and bibliography study method. Data processed with Gross Margin analysis and Linear Programming. Result of Gross Margin analysis indicate that highest earnings obtained by tomato in Cropping Season 1, the lowest earning obtained by cabbage Cropping Season of MT 2, while the actual gross margin is Rp 34,346,985.12. Based on result of optimization using the program of BLPX88, maximum earnings that can be obtained is equal to Rp 35,166,200.00 with the average 0.444 ha of the land cultivated per years by planting chili in Cropping Season 1, Cropping Season 2, Cropping Season 3; tomato in Cropping Season 1, Cropping Season 2, Cropping Season 3, gumitir flower in Cropping Season 1, Cropping Season 2, Cropping Season 3, cabbage in Cropping Season 2, and cattle rearing yearly. Respondents suggested that to apply optimal integrated farming system as according to result of analysis of optimization so that the farmers get maximum results. Besides, the respondents suggested not to rent labors because the labors in family still available. Keywords: optimalization, diversified farm enterprise system, gross margin, linear programming.